PENGARUH PELAKSANAAN PROMOSI DAN CITRA PERUSAHAAN TERHADAP MINAT KONSUMEN (STUDI PADA HOTEL GRAND SUKA PEKANBARU) - Rosnidar Silviana N; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Grand Suka Hotel Pekanbaru is one of the 3 (three) star hotels in Pekanbaru and is located on Jl. Soekarno Hatta Kav.148 Pekanbaru, Riau. The purpose of this study was to determine the effect of Promotion Implementation and Corporate Image (Case Study at Grand Suka Hotel Pekanbaru). The population in this study were all consumers who purchased rooms at Grand Suka Hotel Pekanbaru in the last years, 2019. The sampling technique used the slovin test with the chance sampling method and obtained a sample of 100 respondents. In this research, the method used is descriptive quantitative analysis with SPSS program. Data processing using IBM SPSS 23 statistics. The results of this study indicate that the results of the first t test hypothesis testing, the implementation of promotions on consumer interest is t count (3.775) > t table (1.6605), meaning that the implementation of promotions has a significant effect on consumer interest. Second, the company's image on consumer interest is t count (4,403) > t table (1,6605) meaning that company image has a significant effect on consumer interest. The results of the f test Promotion and company image have a significant effect on consumer interest, namely f count (12.009) > F_table (3.09).Keywords: Implementation of Promotion, Company Image, Consumer Interests